The effect of rhythmic pattern on short term memory of 10 digit recall between music and non-music undergraduate students / Tam Joo Ee - Tam, Joo Ee (2016)

(untitled)
Contentious issues on the perception of musical elements such as melody as a mnemonic device on verbal memory has been widely discussed particularly in the field of education and clinical used. However, research focused on the effect of rhythm, notably on the various type of rhythmic patterns have not fully discovered yet, hence this research attempts to fill the gap in the literature, by testing rhythmic patterns on verbal memory of the recall of ten digit numbers and whether there is a difference between music and non-music major undergraduate students. Methodology included a recall test with 6 sets of 10 digit number and two attempts were given for each rhythmic pattern: no rhythmic pattern, dotted rhythm, inverted dotted rhythm, long short rhythm, short long rhythm and triplets rhythm. Sixty undergraduate students were recruited for this study; thirty musicians from music faculty and thirty non-musicians from non-music faculty. Meanwhile, data were analyzed using SPANOVA. Results revealed that there was a significant difference in 10 digit number recall when the digit is presented with dotted rhythm on 1st attempt [F (df = 1, 118) = 104.47, p < .05)] and 2nd attempt [F (df = 1, 118) = 127.27, p < .05)], inverted dotted rhythm on 1st attempt [F (df = 1, 118) = 19.66, p < .05)] and 2nd attempt [F (df = 1, 118) = 75.73, p < .05)], long short rhythm on 1st attempt [F (df = 1, 118 p < .05) = 34.04] and 2nd attempt [F (df = 1, 118) = 56.13, p < .05)], short long rhythm on 1st attempt [F (df = 1, 118) = 21.98, p < .05)] and 2nd attempt [F (df = 1, 118) = 55.81, p < .05)], triplet rhythm on 1st attempt [F (df = 1, 118) = 9.63 p < .05)] and 2nd attempt [F (df = 1, 118) = 16.54, p < .05)]. Furthermore, There was a significant difference in 10 digit numbers recall between musicians and non-musicians on their short term memory with the aid of different rhythmic patterns on 1st attempt [F (df = 3.6, 206.92) = 5.68, p < .05)] and 2nd attempt [F (df = 1, 58,) = 2.78, p < .05]. Finally, research question 2 was answered using the ANOVA test and result iii indicated there was a significant contrast of different rhythmic patterns on 10 digit numbers recall on 1st attempt [(df = 4, 295) = 17.809, p < .05)] and 2nd attempt [(df = 4, 295) = 10.507, p < .05]. The finding implied that rhythmic patterns aid in digit recalling and the process of rehearsal enhances verbal working memory on both musicians and non-musicians, however musicians scored better as compared to non-musicians according to the result.